2018
DOI: 10.3389/fimmu.2018.02227
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myeloid Leukemia Cells Express ICOS Ligand to Promote the Expansion of Regulatory T Cells

Abstract: CD4+CD25+Foxp3+ regulatory T cells (Tregs) accumulate in bone marrow microenvironment in acute myeloid leukemia (AML). However, little is known about how the tumor environment including tumor cells themselves affects this process. Here we demonstrated that AML cells expressed inducible T-cell costimulator ligand (ICOSL) that can provide costimulation through ICOS for the conversion and expansion of Tregs sustaining high Foxp3 and CD25 expression as well as a suppressive function. TNF-a stimulation up-regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 34 publications
2
69
0
1
Order By: Relevance
“…Furthermore, melanoma patients who received high‐dose IL‐2 therapy exhibited a selective expansion of ICOS + Treg populations which correlated with poor prognosis . Similarly, human acute myeloid leukemia cells expressing high levels of ICOSL promote Treg responses . Second, ICOS promotes the expansion, survival, and cytokine production of inflammatory lung ILC2 cells in animal models of asthma .…”
Section: Implications Of Multifaceted Icos Functions In Cancer Immunimentioning
confidence: 99%
“…Furthermore, melanoma patients who received high‐dose IL‐2 therapy exhibited a selective expansion of ICOS + Treg populations which correlated with poor prognosis . Similarly, human acute myeloid leukemia cells expressing high levels of ICOSL promote Treg responses . Second, ICOS promotes the expansion, survival, and cytokine production of inflammatory lung ILC2 cells in animal models of asthma .…”
Section: Implications Of Multifaceted Icos Functions In Cancer Immunimentioning
confidence: 99%
“…They have been found to work in conjunction with AML by creating a localized zone where HSPC can reside on the endosteal surface and improve their survival [58]. Studies have shown accumulation of Tregs in the bone marrow in AML [59]. Han et al showed that AML can express a Treg costimulatory ligand ICOS-L, activating Tregs directly, and they can also induce some CD4 + cells to become inducible Tregs.…”
Section: T Cellsmentioning
confidence: 99%
“…The AML microenvironment favors the expansion of Tregs (37,(63)(64)(65). Expression of inducible T cell co-stimulator ligand (ICOSL) on AML blasts stimulates T cells through inducible T cell costimulator (ICOS), leading to differentiation to Treg phenotype and expansion of the Treg subset (66). Additionally, AML blasts and bone marrow mesenchymal cells overexpress IDO, which promotes the emergence of a Treg phenotype and limits T cell proliferation (67).…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…While the presence of AML blasts can stimulate monocytes to secrete proinflammatory cytokines including tumor necrosis factor-α (TNFα), IL1β, and IL6, they also cause increased production of the anti-inflammatory cytokine IL10 (93). Additionally, increased Treg subsets contribute to production of IL10 and transforming growth factor β (TGF-β), which can limit the effector function of CAR T cells (66). In analysis of CD123-CAR T cells targeting AML, TNF-α and IFN-γ upregulate CD123 expression on endothelial cells, increasing risk for capillary leak.…”
Section: Anti-inflammatory Cytokines and Chemokinesmentioning
confidence: 99%